2018
DOI: 10.1111/jels.12198
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Physicians: The Effect of Licensing and Liability Laws on the Supply of Nurse Practitioners and Physician Assistants

Abstract: The increased use of nurse practitioners (NPs) and physician assistants (PAs) represents an important option for increasing access to healthcare. I explore the effect of two types of laws on the supply of NPs and PAs: occupational licensing laws that limit the practices of NPs and PAs and caps on noneconomic damages. Relaxing licensing laws to allow NPs to practice with less physician oversight increases the supply of NPs in areas with few practicing physicians by 60 percent—though the size of this increase de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
0
27
1
Order By: Relevance
“…Even when de‐licensing or exempting an occupation from licensure is not an available policy option, research suggests other reform options still benefit market participants. For example, studies of occupations such as nurse practitioner, cremator, and physician assistant have shown relaxing scope‐of‐practice laws results in lower prices for consumers (Kleiner et al ; Ellig ; Timmons ) and an increased supply of workers in areas with shortages (McMichael ). Another type of reform – providing alternative routes to licensure – has also shown efficacious results.…”
Section: Introductionmentioning
confidence: 99%
“…Even when de‐licensing or exempting an occupation from licensure is not an available policy option, research suggests other reform options still benefit market participants. For example, studies of occupations such as nurse practitioner, cremator, and physician assistant have shown relaxing scope‐of‐practice laws results in lower prices for consumers (Kleiner et al ; Ellig ; Timmons ) and an increased supply of workers in areas with shortages (McMichael ). Another type of reform – providing alternative routes to licensure – has also shown efficacious results.…”
Section: Introductionmentioning
confidence: 99%
“…The dates of legislative changes in NP schedule II independent prescriptive authority were compiled through the review of individual state legislatures and cross-validated with several other sources (McMichael, 2017;Traczynski & Udalova, 2018). Figure 1 identifies the states that adopted these laws before or during the period considered in this analysis.…”
Section: Datamentioning
confidence: 99%
“…And clinical evidence has demonstrated that NPs perform as well or better than physicians in delivering care within their education and training (Newhouse et al 2011;Naylor and Kurtzman 2010;Stanik-Hutt et al 2013;Mafi et al 2016;Conlon 2010;Venning et al 2000;Jiao et al 2018;Kuo et al 2015). Relative to physicians, NPs are more likely to practice in primary care specialties, to provide care to Medicaid beneficiaries, and to provide care for rural and underserved populations (McMichael 2018;Stange 2014;DesRoches 2017;Larson et al 2003;Grumbach et al 2003;Everett et al 2009).…”
Section: Nurse Practitioners and Scope-of-practice Lawsmentioning
confidence: 99%
“…When NPs can practice without any physician supervision and prescribe a full range of medications, they can practice independently. Prior work has shown that granting NPs more autonomy can facilitate access to care (Graves et al 2016;McMichael 2018;Traczynski and Udalova 2018), improve the quality of care (Traczynski and Udalova 2018), reduce the use of intensive medical procedures (Markowitz et al 2017), and reduce the price of some healthcare services (Kleiner et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation